PS02.141: RESULTS AND PROSPECTS OF SALVAGE SURGERY AFTER DEFINITIVE CHEMORADIOTHERAPY FOR ESOPHAGEAL CANCER. (14th September 2018) - Nabeya, Yoshihiro; Hoshino, Isamu; Nagata, Matsuo; Takiguchi, Nobuhiro; Ikeda, Atsushi; Soda, Hiroaki; Tonooka, Toru; Gunji, Hisashi; Yoshizumi, Arihito; Imazeki, Hiroshi; Minashi, Keiko; Hironaka, Shuichi
Abstract: Background: Salvage surgery for esophageal cancer (squamous cell carcinoma) patients with locoregional failure after definitive chemoradiotherapy (dCRT) is high risk, and no surgical consensus has been established. We evaluated our 2 procedures of salvage surgery for failure which was confirmed by GS, CT, and PET: [SE] esophagectomy followed by reconstruction for patients ≤ 80 yo, without cT4 at the initial presentation, and whose recurrent/residual tumor can be removed as a R0 resection, and [SL] dissection of only metastatic abdominal lymph nodes for patients without any other failure. Methods: All patients received dCRT ≥ 50 Gy followed by salvage surgery. In 17 patients who underwent SE from 2009 to 2014, prophylactic dissection of cervical or 106 tbL nodes was often omitted, poststernal route was preferred, Ligasure TM was routinely used, and aggressive nutritional intervention with enteral nutrition was perioperatively supplied. In SL for 5 patients until 2016, No. 3 and 7 nodes were removed. Results: [SE] Sixteen patients received R0 resection. Postoperative complications were noted in 6 patients (35%), and pleural effusion was the most common (24%). However, neither anastomotic leakage nor in-hospital death developed. Median overall survival (OS) time is 44 months, and provisional 5-year OS rate is 41%. While 7 patients died of esophageal caner, one died from another caner and 3 died from other illness. Tentative 5-year disease-free survival (DFS) rate is 54%. Between cases with relapse after CR and cases with residual tumor, no significant difference was found in postoperative recurrence (2/8 vs. 5/9, P = 0.33) and survival (provisional 5-year OS rate: 50 vs. 33%, P = 0.45/provisional 5-year DFS rate: 70 vs. 40%, P = 0.22), while the relapsed patients after CR showed a little better outcome. [SL] Three patients have no relapse for 60/36/18 months after SL. One developed bone metastasis in 54 months after SL. One patient developed repeated abdominal recurrence and underwent SL again. Conclusion: SE can be safely performed with strict planning, secure surgery and appropriate perioperative care. SL can also be beneficial as a less invasive salvage surgery to selected patients. Strict decision-making and appropriate postoperative follow-up method with attention to other diseases should be established based on further studies. Disclosure: All authors have declared no conflicts of interest.